Daya Terima Konsumen terhadap Inovasi Unik Produk Makanan Sambal Tabur Kecombrang - Laili Nabila Artanti, Hana; Ramadhani, Annisa Nurul; Nuzula, Zahra Firdausi; Rohmawati, Ovik Azahra; Gunalaing, Emiliana Siwu; Asmaul, Rina (STKIP PGRI SITUBONDO, 2024)
This research aims to determine consumers' acceptance of quality which includes taste and texture as well as packaging and price of the unique product innovation